LEPTIN’s LEVEL AND ITS RELATIONSHIP TO ANTHROPOMETRICAL PARAMETERS IN PATIENTS WITH ACROMEGALY - Mykytyuk, M.R.; Khizhnyak, O.O. (World of Medicine and Biology, 2014)
The study involved 60 patients with active acromegaly. Shown that leptin levels in patients with acromegaly, regardless of gender associated with both BMI and from Fat,%; leptin levels in women are also associated with OT and OS. In the total sample of patients with acromegaly were found significant effect of excessive production of growth hormone and IRF -1 production of leptin and its sexual dimorphism. The level of leptin significantly associated with the level of growth hormone in the blood only in women. The level of leptin in patients with somatotropinomoyu leptin level is associated with the level of PRL levels.
Keywords: acromegaly; growth hormone; insulin-like growth factor -1; prolactin; leptin